Acquired Arteriovenous Fistulae: A Study of Three Cases and Review of Literature - Amit Mahajan; Anil Luther (Indian Journal of Vascular and Endovascular Surgery, 2016)
William Hunter is credited with the earliest description of an arteriovenous fistula (AVF) when he noticed an abnormal connection between an artery and a vein in two patients who underwent a phlebotomy. After the 19 th century with the advent of high-speed projectiles, the incidence of AVF increased. With a better understanding of the underlying pathophysiology, the modalities of diagnosis and treatment have come a long way and even now continue to change. We present below three patients who presented with AVF and were treated with surgery.